A inserção das pessoas com deficiência visual no mercado de trabalho: um estudo em empresas da Região Metropolitana de Belém no período de 2000 a 2006 - MORAES, Liliane Vieira (Universidade Federal do Pará, 2012)
This work investigates the insertion of people with visual deficiency in the labor market focusing on private companies in the Metropolitan area of Belém, from 2000 to 2006. Labor market is considered in this study as a complex system which results from the predominant rules of the relationship between capital and work. However, at the same time, there are insertion mechanisms based on criteria which are not always explicit and that can lead to discriminatory outcomes. The research was mainly based on data collected from private companies of the Metropolitan Region of Belém. This research shows that, throughout that period, the insertion of people with visual deficiency in the labor market in Belém was short, and that there was a significant disparity between the insertion of people with low vision and blind ones, the latter being almost non-existent in private companies within the Metropolitan Region of Belém.